Citizens’ preference for e-participatory governance - Oluwafemi Victor Oludu; Tuğberk Kaya; Damla Karagozlu (PLoS ONE, 2025)
This paper investigates the preference, adoption, and utilization of e-government services among the citizens of Nigeria through preferred social media. Adopting a quantitative methodology approach with 1000 samples from various local governments and Statistically Analyzing the data, the research explores the extent to which Nigerian citizens have embraced e-government initiatives through social media and the factors influencing their adoption. Questions focusing on the availability of e-government platforms, social media e-governance, and e-participation level based on trust in government, the most preferred social media for e-participation were considered. Findings reveal varying levels of e-government adoption across different local government authorities, influenced by factors such as infrastructure limitations, institutional capacity, and political will, also a high level of participation through various social media platforms was observed, and the level of correlation between government trust and e-participation using the available platforms was found to be minimal. The paper contributes to the understanding of e-government implementation in the Nigerian context, offering insights into strategies for enhancing the effectiveness and sustainability of e-government initiatives at the local government level using social media Platforms.